2003
DOI: 10.1016/s0272-7358(03)00071-0
|View full text |Cite
|
Sign up to set email alerts
|

College students and problematic drinking: A review of the literature

Abstract: Problem drinking during the college years is a significant public health concern. The goal of the current review was to examine the primary psychosocial factors that predict problem drinking in college students. Variables examined included demographic variables, personality, drinking history, alcohol expectancies, drinking motives, stress and coping, activity involvement, and peer and family influence. Evidence from studies of college drinking indicated that the variables associated with college drinking seem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
459
2
26

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 599 publications
(515 citation statements)
references
References 129 publications
(276 reference statements)
28
459
2
26
Order By: Relevance
“…Even light drinking levels for this group could have the potential for later health consequences because of the association between acetaldehyde (a toxin) and esophageal cancer (33). It is likely, based on earlier studies, that these students are not drinking one drink nightly over the month but instead are drinking at higher rates during the weekend or other social engagements (28,34). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even light drinking levels for this group could have the potential for later health consequences because of the association between acetaldehyde (a toxin) and esophageal cancer (33). It is likely, based on earlier studies, that these students are not drinking one drink nightly over the month but instead are drinking at higher rates during the weekend or other social engagements (28,34). …”
Section: Discussionmentioning
confidence: 99%
“…An elevated level of peer drinking is apt to enable a more permissible environment for drinking (11). Ham and Hope (34) identified higher perceived drinking norms and increased alcohol availability as factors that facilitate drinking in college settings. Drunken behavior among college students is often memorable and subsequently talked about with friends, which can inflate drinking norms (28).…”
Section: Discussionmentioning
confidence: 99%
“…Two recent systematic reviews have reported follow-up outcomes at 6 months or longer. However, they did not analyze college student and noncollege adult trials separately (13,17), despite distinctions between these groups in patterns of alcohol consumption and associated impairment (18,19). In addition, previous systematic reviews have generally not reported on the efficacy of e-interventions for AUDs (13)(14)(15)(16)(17) or provided detailed descriptions of treatment intensity, including amount and type of human support (13)(14)17).…”
Section: Primary Funding Source-us Department Of Veterans Affairsmentioning
confidence: 99%
“…Although both groups were demographically comparable, gender was included in all analyses since previous research has shown gender to be related to drinking behavior among college students (Ham & Hope, 2003).…”
Section: Analysis Strategymentioning
confidence: 99%